2016
DOI: 10.14393/bj-v32n1a2016-26249
|View full text |Cite
|
Sign up to set email alerts
|

Health and quality of zinc coated wheat seeds during storage

Abstract: ABSTRACT:The objective was to evaluate the effect of seed wheat coated with zinc, in its physiological, sanitary attributes and enzyme quality, during storage. We used two batches of seed, for seed treatment, we used commercial product as a source of zinc in the form of ZnSO 4 , along with fungicide and polymer. It was tested for levels 0, 1, 2, 3 and 4 mL ZnSO 4 kg -1 seed. The physiological quality, during the storage period, was analyzed by the tests: moisture content, hectoliter weight, germination, emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Similarly, Bittencourt et al (2000) reported a moisture content reduction in maize seeds, as a function of the low relative humidity values during 30 days of storage with difference of 0.5% between thiamethoxam seed treatment and untreated seeds at first 15 days of storage. However, Tunes et al (2016) observed that the moisture content of wheat seeds was not influenced by treatment with different doses of zinc sulfate (ZnSO 4 ) + fungicide (carboxin + thiram) + polymer applied using a syrup spray volume of 15 mL. kg -1 , and stored for six months under non-controlled environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Bittencourt et al (2000) reported a moisture content reduction in maize seeds, as a function of the low relative humidity values during 30 days of storage with difference of 0.5% between thiamethoxam seed treatment and untreated seeds at first 15 days of storage. However, Tunes et al (2016) observed that the moisture content of wheat seeds was not influenced by treatment with different doses of zinc sulfate (ZnSO 4 ) + fungicide (carboxin + thiram) + polymer applied using a syrup spray volume of 15 mL. kg -1 , and stored for six months under non-controlled environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Resultados similares han sido informados por Funguetto [30] para semillas de arroz recubiertas con zinc, un fungicida y un polímero, o por Lemes, et al [31], para semillas de trigo recubiertas con zinc, un fungicida y un polímero. Por otro lado, de Tunes, et al [32] [36] encontraron una reducción en el porcentaje de germinación para semillas de sorgo tratadas con zinc. Las diferencias entre los resultados descritos anteriormente podrían explicarse por las diferencias entre los cultivos en términos de eficiencia de uso de los nutrientes [31].…”
Section: Tratamientounclassified